Next generation sequencing for detection of EGFR alterations in NSCLC: is more better?. Issue 3 (28th December 2020) - Batra, Ullas; Nathany, Shrinidhi; Sharma, Mansi; Jain, Parveen; Mehta, Anurag
Abstract : Aims: The emergence of sophisticated next generation sequencing (NGS) based technologies in routine molecular diagnostics has paved the way for robust and accurate detection of variants which may otherwise be missed on single gene testing. This study aims at highlighting the same premise in EGFR mutated non-small cell lung carcinoma (NSCLC). Methods: 1350 cases of NSCLC were screened, of which 490 EGFR mutated cases were taken. The clinical records and molecular features were evaluated retrospectively to determine those cases which were missed on single gene testing. Results: Among these 490 cases, there were 11 (2.2%) cases which tested negative on single gene testing using polymerase chain reaction (therascreen). These were then subjected to NGS based testing and were positive for 13 different EGFR mutations. Five out of the 11 cases received EGFR tyrosine kinase inhibitor (TKI) based on the NGS test outcome. Four cases with exon 20 insertion mutations were not offered TKI as these mutations are known to be intrinsically resistant to TKI therapy. The five patients who have been treated with TKI have shown fair response and have not progressed to date. Conclusions: We demonstrated a potentially preferable way to profile treatment-naïve patients with NSCLC by NGS and from our early experience in EGFR mutant cases, the advantages of NGS over single gene testing is clearly evident.